Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan Bagian Produksi Pada CV. Cynthia Box Kudus - Utami, Dewi Putri; Rodhiyah, Rodhiyah; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2016)
: Every organization which is serving the public importanceof State-owned or private organization, want to get maximum achievement related to the employee’s performance, improvement result and attain the goal of the organization. From the performance’s appraisal there is still unfulfilled working standard and the lack of the provision of the facilities provided by the company The aim of the study is determine the effect of working environment toward employee’s performance at CV. Cynthia Box Kudus.The tipe of the study is explanatory,which is the technique of collecting data through questionnaires, with 45 samples of employees from the production division and the research took all of them, or simple called as saturated sample. Methode of analysis used in this study is Quantitative Data Analysis. This research uses some data analytical methods, such as validity test, reliability test, correlation test, coefficient of determination test, simple linear regression, multiple linear regression, t-test, and F-test, which are supported by SPSS 15.00. The results and discussion of this study found that categorization of the good working environment and the mean variabel score is 3,50. However, in the assessment of the work environment there is still not well under the average of which is about a smooth communication and levels of air temperature in the workplace. T-test value is 3,780 > t-table 2,0167. The corellation between working environment and employee’s performance is intermediate. The regression coefficient of working environment is 0,109 and its coefficient of determination is 24,9%. The categorization of compensation is good enough and the mean variabel score is 3,69. However, in the assessment of compensation there is still not well under the average of which is about the suitability of the amount of overtime pay. T-test value is 1,758 < t-table 2,0167. The corellation between compensation and employee’s performance still need some improvement. The regression coefficient of compensation is 0,302 and its coefficient of determination is 6,5%. The categorization of employee’s performance is good enough and the mean variabel score is 3,66. F-test value is 7,071 < F-table 3,22. The Conclusions and suggestions work environment partially influence on employee performance, whereas partial compensation does not influence the employee’s performance.However, the working environment and compensation are tested simultaneously and there is an influence on employee’s performance. Suggestion for the company, they should keep the company facilities and improve the work environment and still maintain consistency in giving welfare for the employees in order to improve employees performance.